Scientific Writing and Project-Based Learning Planning Based on a Deep Learning Approach - Doni Pranata; Yusawinur Barella; Dina Fitriana; Sutoyo Budiharto; Malisa Chorina (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Faculty of Teacher Training and Education (FKIP) is one of the faculties at Tanjungpura University that serves as a platform for prospective teachers to study learning theories and their application in society. As future educators, students are expected to be active in writing, both in the form of papers and scientific articles. When they become teachers, they are still required to conduct research and are expected to continue producing scientific writing. However, teachers often feel confused about how to start writing, and many common issues arise, such as errors in writing, inconsistencies with article guidelines, and improper use of language conventions. These problems lead to delays in publication due to lengthy revision processes, and some manuscripts are even rejected. Therefore, this training is organized to guide teachers in writing articles and tailor them to the needs of project-based learning aligned with a deep learning approach. Through this program, teachers will gain knowledge about comprehensive scientific writing and subsequently align it with their preferred learning themes.